Pengembangan Media Pembelajaran Berbasis Instragram Menulis Teks Eksposisi Proses - Zathu Restie Utami (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this study: (1) to determine the development of learning media based on Instagram features in learning exposition text writing skills for grade VII junior high school students; (2) to describe the feasibility of learning media based on Instagram features in learning exposition text writing skills for grade VII junior high school students; and (3) to describe the practicality of learning media based on Instagram features in learning procedural text writing skills for grade VII junior high school students. The subjects of this study were grade VII students. The development eksposisi was carried out through four stages, namely define, design, develop, disseminate. Data collection techniques used observation, interviews, questionnaires, pretests and posttests. The results of this study indicate: (1) the process of developing learning media based on Instagram features was carried out in stages, namely (a) definition, (b) design, (c) development and (d) implementation. (2) Learning media based on Instagram features developed for learning exposition text writing skills for grade VII students with the 4-D model (Define, Design, Develop, Disseminate) is feasible to be used as learning media. The results of the assessment by media experts who obtained a score of 3.4 t and the assessment by material experts of 3 are included in the good category. (3) Instagram feature-based learning media developed for grade VII junior high school students in expository text writing skills learning is stated to be practical for use in learning.